Optic Perineuritis in Behçet Disease. Issue 4 (December 2015) - Lai, Chuntao; Sun, Yanbin; Wang, Jiawei; Purvin, Valerie A.; He, Yunhong; Yang, Qinglin; Jing, Yun; Yin, Hongxia; Zhu, Jing
Abstract : Background: Optic perineuritis (OPN), an uncommon optic neuropathy, has previously not been described in patients with Behçet disease (BD). We conducted this study to describe the clinical features, response to treatment, and outcome of OPN due to BD, with particular emphasis on those features that might distinguish this from the idiopathic variety. Methods: This is a retrospective, case series review of all patients with a diagnosis of OPN seen in a hospital-based neurology department from 2008 to 2014 who also met the international criteria for the diagnosis of BD. Results: Twenty-one patients with OPN were identified, of whom 10 (12 eyes) met the criteria for BD. OPN developed 2–10 years (mean, 4 years) after onset of BD, but the diagnosis of BD was made only after onset of OPN in 6. Nine of 12 eyes (75%) had severe visual loss (⩽20/200), and 80% of patients progressed over several days from onset. After high-dose corticosteroid treatment, all patients experienced relief of pain, and 5 patients (50%) showed improved visual acuity. At last follow-up (mean, 25 months) 7 of 11 (64%) of affected eyes had good visual outcome (≥14/20), and no patient experienced a subsequent neurological event. Conclusions: OPN may occur as a manifestation of BD and, in non-Western countries, this may be more common than the idiopathic variety. In contrast to idiopathic cases, OPN in BD is more likely to demonstrate initial rapid progression of visual loss and more severe loss at presentation. Patients show less recovery of vision in response to corticosteroids but carry a lower rate of subsequent relapse. Patients with OPN should be specifically questioned regarding symptoms of BD.